New perspectives on economic development a human agency approach - Yu, Fu-Lai Tony 1950-; SpringerLink (Online service). (Wageningen Wageningen Academic Publishers, 2011)
This book is the first of its kind to use Austrian subjectivism to analyze issues in economic development. Unlike scholars in mainstream neoclassical economics who explain economic development by quantitative growth models, this book attempts to understand economic progress in human agency perspective. In this approach, human agency is placed at the centre of economic analysis. This book begins with a review of the theories of economic development in the history of Austrian economics, with the intention of extending the contributions of major Austrian economists to development economics. After pointing out the weaknesses in the orthodox neoclassical approach to economic growth, the book then puts forward a subjectivist methodology which integrates the contributions of Max Weber, Alfred Schutz and Austrian Economists to interpret economic phenomena and policies. This chapter also serves as a methodological foundation for arguments elaborated in subsequent chapters. The rest of the book discusses important issues in economic development, namely, entrepreneurial process, national capabilities, innovation, trade, government, transition and catching up strategies for firms in latecomer economies. The book ends with concluding remarks and a proposal for a new research agenda in economic development. This book is well written, free from mathematics and is highly readable. It adds new insights not only in economics, but also in management, politics and social sciences. It will be useful to scholars, policy makers and students in economic development, entrepreneurship, theory of the firm, management of innovation, government policy, economic sociology, Austrian and evolutionary economics.
Electronic reproduction.
Keywords: Economic development; Economics -- Philosophy; Austrian school of economics; Entrepreneurship; Electronic books